Negative electrode pre-lithiation method and lithium ion battery

A pre-lithiation method using a fluorocarbonate additive and aromatic compounds in the electrolyte accelerates lithium embedding and forms a stable SEI film, addressing the slow embedding and instability issues in silicon anodes, thereby enhancing lithium-ion battery performance.

CN119230964APending Publication Date: 2024-12-31AESC DYNAMICS TECHNOLOGY (ORDOS) LTD +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411660567.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Current pre-lithiation methods for silicon anodes in lithium-ion batteries face slow lithium embedding rates, leading to lithium precipitation and SEI film instability, which deteriorate battery performance and cycle life, especially under high temperatures.

Method used

A pre-lithiation method involving the formation of a lithium metal film on the negative electrode using a specialized electrolyte containing a fluorocarbonate additive and aromatic compounds, which accelerates lithium embedding and forms a stable SEI film, reducing lithium precipitation and improving battery performance.

Benefits of technology

The method significantly shortens pre-lithiation time, enhances the stability of the SEI film, and improves the overall performance of lithium-ion batteries, including impedance, room temperature cycle, and high temperature storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230964A_ABST
    Figure CN119230964A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, in particular to a negative electrode pre-lithiation method and a lithium ion battery. The negative electrode pre-lithiation method comprises the following steps: a film forming step: forming a lithium metal film on the surface of a negative electrode piece; and a formation step: standing the negative pole piece with the lithium metal film in an electrolyte to obtain a pre-lithiated negative pole piece. An electrolyte in the formation step comprises an organic solvent, a lithium salt, a diluent and an additive. The lithium salt is dissolved in the organic solvent, and the mass fraction of the lithium salt in the electrolyte is 10%-20%; the diluent is a substituted or unsubstituted aromatic compound, and the mass fraction of the diluent in the electrolyte is 20-50%; the additive is a fluoro-carbonate additive with the reduction potential higher than that of the organic solvent, and the mass fraction of the additive in the electrolyte is 1%-20%. The negative pole piece of the lithium ion battery prepared by the method can improve the circulation of the lithium ion battery and reduce the side reaction of the battery at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of secondary batteries, and in particular to a negative electrode pre-lithiation method and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are one of the most widely used batteries on the market and are widely used in mobile devices, power tools, aerospace and other fields, especially in the fields of electric vehicles and large-scale energy storage.

[0003] As application scenarios continue to expand, consumers have higher demands for the energy density of lithium-ion batteries. In the current research field, developing negative electrodes with high initial efficiency is an important way to achieve high specific energy lithium-ion batteries.

[0004] Research shows that for silicon anodes with high specific capacity, their initial efficiency is much lower than that of graphite anodes, so pre-lithiation of silicon anodes is the key to further improving the energy density of lithium-ion batteries. Among them, pre-lithiation of silicon anodes with lithium metal is currently the best way to improve battery energy density, because this method hardly introduces irrelevant components that can occupy the weight of the battery.

[0005] At present, the pre-lithiation method of the negative electrode is to attach lithium foil to the surface of the negative electrode plate by rolling or to deposit metallic lithium on the surface of the negative electrode plate by physical vapor deposition (PVD) to complete the pre-lithiation. However, this pre-lithiation method faces two problems: on the one hand, the rate of metallic lithium embedding into the negative electrode is slow, and the negative electrode needs to be pre-lithiated by standing for a long time. At the same time, metallic lithium will remain on the surface of the negative electrode plate as a lithium precipitation site, destroying the negative electrode solid electrolyte interface (Solid Electrolyte Interface, SEI), causing the electrolyte to undergo a reduction reaction, and the increase in local polarization will further lead to lithium precipitation, and ultimately cause a series of problems such as lithium loss and rapid capacity decay in lithium-ion batteries. On the other hand, the pre-lithiated negative electrode plate will immediately undergo a lithium insertion reaction to generate an SEI film after the electrolyte is injected. The mechanical properties and chemical stability of the SEI film will directly affect the performance of the battery, especially under high temperature conditions, the stability of the SEI becomes worse, and then the high temperature resistance of the battery decreases. The above problems will lead to a significant deterioration in the rate performance of the battery and a significant decrease in the cycle life. Summary of the invention

[0006] In view of the above problems, the present invention provides a negative electrode pre-lithiation method and a lithium-ion battery. The negative electrode pre-lithiation method can not only significantly shorten the pre-lithiation time, but also improve the stability of the SEI film and improve the overall performance of the lithium-ion battery including at least one aspect of the first effect, impedance, room temperature cycle and high temperature storage.

[0007] One aspect of the present invention provides a negative electrode pre-lithiation method, comprising the following steps:

[0008] The film forming step forms a lithium metal film on the surface of the negative electrode.

[0009] In the formation step, the negative electrode sheet with the lithium metal film is placed in an electrolyte to obtain a pre-lithiated negative electrode sheet.

[0010] The electrolyte used in the formation step includes an organic solvent, a lithium salt, a diluent and an additive. The lithium salt is dissolved in the organic solvent, and its mass fraction in the electrolyte is 10%-20%; the diluent is a substituted or unsubstituted aromatic compound, and its mass fraction in the electrolyte is 20-50%; the additive is a fluorocarbonate additive with a reduction potential higher than that of the organic solvent, and the mass fraction of the fluorocarbonate additive in the electrolyte is 1%-20%.

[0011] Optionally, the fluorinated carbonate additive is fluorinated ethylene carbonate, and the mass fraction of fluorinated ethylene carbonate in the electrolyte is 1-10%.

[0012] Optionally, in the film forming step, a lithium metal film is formed on the surface of the negative electrode plate by physical vapor deposition or roll-compression lamination, and the thickness of the lithium metal film is 0.5-10 μm.

[0013] Optionally, in the formation step, a prescribed standing temperature is used for a prescribed time, the prescribed standing temperature is 25° C.-60° C., and the prescribed time is 24 h-96 h.

[0014] The second aspect of the present invention provides a lithium-ion battery, including a negative electrode plate, a positive electrode plate and an electrolyte. The negative electrode plate and the positive electrode plate are separated and arranged in the electrolyte, and the surface of the negative electrode plate has a pre-lithiation layer, and the pre-lithiation layer is obtained by using the lithium metal film covering the surface of the negative electrode plate to be formed in the electrolyte. The electrolyte includes an organic solvent, a lithium salt, a diluent and an additive. Among them, the lithium salt is dissolved in the organic solvent, and its mass fraction in the electrolyte is 10%-20%; the diluent is a substituted or unsubstituted aromatic compound, and its mass fraction in the electrolyte is 20-50%; the additive is a fluorocarbonate additive with a reduction potential higher than that of the organic solvent, and the mass fraction of the fluorocarbonate additive in the electrolyte is 1%-20%.

[0015] Optionally, the fluorinated carbonate additive is fluorinated ethylene carbonate, and the mass fraction of fluorinated ethylene carbonate in the electrolyte is 1-10%.

[0016] Optionally, the diluent includes any one of fluorobenzene, o-difluorobenzene, m-difluorobenzene, p-difluorobenzene, 1,3,5-trifluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, trifluoromethylbenzene, toluene, and ethylbenzene, or a combination of at least two thereof.

[0017] Optionally, the organic solvent includes any one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate, or a combination of at least two thereof, and the mass fraction of the organic solvent in the electrolyte is 30%-65%.

[0018] Optionally, the positive electrode plate includes a positive electrode current collector and a positive electrode active material, wherein the positive electrode active material includes any one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, or a combination of at least two thereof.

[0019] Optionally, the negative electrode plate includes a negative electrode current collector and a negative electrode active material, wherein the negative electrode active material includes any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxides, silicon carbon compounds or lithium titanate, or a combination of at least two thereof.

[0020] The negative electrode pre-lithiation method provided in some examples of the present invention can increase the speed of lithium metal embedding into the negative electrode by using a functionalized electrolyte on the one hand; on the other hand, it helps to form a stable interface SEI film, improve the cycle capacity of the lithium-ion battery, and reduce the occurrence of side reactions of the lithium-ion battery at high temperatures.

[0021] Specifically, the diluent in the electrolyte does not participate in the solvation of lithium ions, but can improve the ability of lithium salt anions to form ion pairs with lithium ions, so that they can be further reduced on the surface of the negative electrode, thereby forming an SEI film rich in inorganic components such as lithium nitride, lithium fluoride, and lithium sulfide in situ, improving the long-term cycle stability of lithium-ion batteries. When lithium metal contacts the negative electrode, pre-lithiation of the negative electrode using an electrolyte containing a diluent can form a microscopic primary cell, thereby accelerating the process of lithium metal becoming lithium ions and then reacting with the negative electrode, which can greatly shorten the pre-lithiation time.

[0022] In addition, because an appropriate amount of fluorocarbonate additive is added to the electrolyte, the reduction potential of the fluorocarbonate additive is higher than that of the solvent. During formation and charging, a stable SEI component rich in fluorine will first be generated on the surface of the negative electrode, which is beneficial to consume residual lithium metal and avoid lithium precipitation problems caused by residual lithium metal. It can also reduce the impedance of the electrode and improve the high-temperature stability of the SEI film. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Flow chart of the negative electrode pre-lithiation method in an embodiment of the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0026] Solid Electrolyte Interface (SEI): During the charging and discharging process of lithium-ion batteries, the electrode material and the electrolyte react at the solid-liquid interface to form a passivation layer covering the surface of the electrode material.

[0027] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values ​​within the numerical range is considered continuous and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined.

[0028] Figure 1 is a flow chart of the negative electrode pre-lithiation method in an embodiment of the present invention, such as Figure 1 As shown, the first aspect of the present invention provides a negative electrode pre-lithiation method, comprising the following steps:

[0029] Film forming step S1, forming a lithium metal film on the surface of the negative electrode plate;

[0030] In the formation step S2, the negative electrode sheet having the lithium metal film is placed in an electrolyte to obtain a pre-lithiated negative electrode sheet.

[0031] The film forming step S1 can use physical vapor deposition (PVD) technology to deposit a lithium metal film on the surface of the negative electrode sheet. Preferably, the thickness of the lithium metal film is 0.5-10 μm. Specifically, the PVD method used can be a resistance thermal evaporation method. In other embodiments of the present invention, ultra-thin lithium foil and negative electrode sheets can also be rolled and compounded to transfer the lithium foil to the negative electrode sheet to complete the preparation of lithium-containing negative electrode sheets. The preferred thickness is 0.5-10 μm. This thickness range can take into account the amount of lithium metal, the rate of pre-lithiation, and the quality of the SEI film.

[0032] Next, after the lithium-containing negative electrode sheet, positive electrode sheet and separator are assembled into a dry battery cell, the formation step S2 is performed. An electrolyte with a pre-lithiation function is used for injection, and the electrolyte is placed at a specified standing temperature for a specified time, wherein the standing temperature is preferably 25°C-60°C, and the standing time is preferably 24h-96h. After the formation step S2 is completed, the lithium-ion battery with pre-lithiation of the negative electrode in the embodiment of the present invention is obtained.

[0033] In the above-mentioned formation step S2, the electrolyte used includes an organic solvent, a lithium salt, a diluent and an additive. Among them, the lithium salt is dissolved in an organic solvent, and its mass fraction in the electrolyte is 10%-20%; the diluent is a substituted or unsubstituted aromatic compound, and its mass fraction in the electrolyte is 20-50%. The diluent itself does not participate in the solvation of lithium ions, and can improve the ability of lithium salt anions to form ion pairs with lithium ions, form an inorganic component SEI film in situ, and improve the cycle stability of lithium ion batteries. When lithium metal contacts the negative electrode, the electrolyte containing the diluent is pre-lithiated to form a microscopic primary cell in the electrolyte, thereby accelerating the process of lithium metal turning into lithium ions and then reacting with the negative electrode. The above process can greatly shorten the pre-lithiation time.

[0034] In an embodiment of the present invention, in order to solve the problem of a small amount of residual lithium in the pre-lithiation process of the negative electrode plate, the additive added to the electrolyte is a fluorocarbonate additive, and the reduction potential of the fluorocarbonate additive is higher than that of the organic solvent, so that a stable SEI component rich in fluorine can be first generated on the surface of the negative electrode during formation and charging, which is conducive to consuming the residual lithium metal and avoiding the problem of lithium precipitation caused by residual lithium. The mass fraction of the fluorocarbonate additive in the electrolyte is preferably 1%-20%. Among them, in some embodiments of the present invention, the fluorocarbonate additive is preferably fluoroethylene carbonate (FEC), and the mass fraction of the fluoroethylene carbonate in the electrolyte is preferably 1-10%.

[0035] The second aspect of the present invention also provides a lithium-ion battery, the negative electrode plate of the lithium-ion battery is prepared by the above-mentioned negative electrode pre-lithiation method, and the lithium-ion battery also specifically includes a positive electrode plate, a separator and an electrolyte. Among them, the negative electrode plate and the positive electrode plate are separated by a separator and arranged in the electrolyte. During the battery charging and discharging process, lithium ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate. The separator is arranged between the positive electrode plate and the negative electrode plate to play an isolation role, and the electrolyte plays the role of conducting ions between the positive electrode plate and the negative electrode plate. The electrolyte specifically includes an organic solvent, a lithium salt, a diluent and an additive.

[0036] In order to improve the dissociation degree of lithium salt and keep the electrolyte with high ionic conductivity and low interface impedance, the embodiment of the present invention preferably uses carbonate solvent as the organic solvent of the electrolyte, and the carbonate solvent includes cyclic carbonate solvent and linear carbonate solvent, specifically including any one or a combination of at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate. More preferably, ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) can be mixed in a mass ratio of 1:2:1:6 to form the organic solvent in the electrolyte of the embodiment of the present invention. The mass fraction of the organic solvent in the electrolyte is preferably 30%-65%.

[0037] The lithium salt is preferably any one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluoroarsenate, or a combination of at least two thereof, and more preferably lithium bis(fluorosulfonyl)imide. The mass fraction of the lithium salt in the electrolyte is preferably 10%-20%, and more preferably, the mass fraction is 16%.

[0038] In the lithium ion battery provided in the embodiment of the present invention, the diluent added to the electrolyte is a substituted or unsubstituted aromatic compound, preferably any one of fluorobenzene, o-difluorobenzene, m-difluorobenzene, p-difluorobenzene, 1,3,5-trifluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, trifluoromethylbenzene, toluene, and ethylbenzene, or a combination of at least two. The above types of diluents themselves do not participate in the solvation process of lithium ions, and can improve the ability of lithium salt anions in the electrolyte to form ion pairs with lithium ions, so that the ion pairs are further reduced on the surface of the negative electrode, and finally form a SEI film rich in inorganic components such as lithium nitride, lithium fluoride, and lithium sulfide. Compared with the formation of an SEI film containing a large amount of organic components in a pure carbonate electrolyte without a diluent, by adding the above diluent to the electrolyte of the lithium ion battery of the embodiment of the present invention, the negative electrode sheet can form a uniform and dense inorganic SEI film in situ, thereby significantly improving the long-term cycle stability of the lithium ion battery. In order to enhance the initial efficiency of lithium-ion batteries and improve their impedance, room temperature cycle and high temperature storage performance, the mass fraction of the diluent in the electrolyte is preferably 20%-50%, more preferably, the mass fraction is 30%.

[0039] In an embodiment of the present invention, the electrolyte of the lithium-ion battery also includes an additive, and the additive includes at least a fluorocarbonate additive having a higher reduction potential than the organic solvent. In addition to being able to solve the problem of a small amount of lithium residue in the pre-lithiation process of the negative electrode plate due to its own reduction potential being higher than that of the organic solvent, the fluorocarbonate additive can also reduce the impedance of the electrode and improve the high temperature stability of the SEI film during the operation of the lithium-ion battery. The mass fraction of the fluorocarbonate additive in the electrolyte is preferably 1%-20%, and the type of the fluorocarbonate additive is preferably fluoroethylene carbonate (FEC). Although the first effect of the lithium-ion battery after adding the FEC additive will be reduced to a certain extent, its life of normal temperature cycle can be improved, and its high temperature performance is also significantly improved. The mass fraction of the fluoroethylene carbonate in the electrolyte is preferably 1-10%, and more preferably, the mass fraction of the fluoroethylene carbonate in the electrolyte is 10%.

[0040] The positive electrode plate of the lithium-ion battery provided in the embodiment of the present invention includes a positive electrode current collector and a positive electrode active material. The positive electrode current collector is usually made of a material with good electrical conductivity and mechanical strength, which is not limited here. In the embodiment of the present invention, aluminum foil is preferably used as the positive electrode current collector. The positive electrode active material may include any one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide, or a combination of at least two. In the lithium-ion battery provided in the embodiment of the present invention, the positive electrode plate is preferably a lithium nickel cobalt manganese oxide positive electrode plate.

[0041] The negative electrode sheet of the lithium-ion battery includes a negative electrode current collector and a negative electrode active material. The negative electrode current collector can be made of a material with good conductivity and mechanical strength, which is not limited here. The present invention preferably uses copper foil as the negative electrode current collector. The negative electrode active material may include any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide compounds, silicon carbon compounds, and lithium titanate, or a combination of at least two of them. Those skilled in the art can choose according to actual needs, preferably a graphite-silicon composite negative electrode sheet.

[0042] The isolation membrane is selected from conventional types in the art, for example, PE or PP porous membrane can be selected as the isolation membrane, the thickness of the isolation membrane is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL; the porosity is 30% to 50%.

[0043] The technical scheme of the present invention is described in detail below through specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.

[0044] The electrolyte compositions of different groups of embodiments and comparative examples are specifically referred to Table 1

[0045] Example 1

[0046] In an argon atmosphere glove box with a water content of <10ppm, battery-grade ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 1:2:1:6 to form an organic solvent. The lithium salt selected in the electrolyte in Table 1 is lithium bis(fluorosulfonyl)imide (LiFSI), and its mass fraction in the electrolyte is 16%; the selected diluent is trifluoromethylbenzene, and its mass fraction in the electrolyte is 30%; the additive is fluoroethylene carbonate (FEC), and its mass fraction in the electrolyte is 10%; in addition to the diluent, additive, and lithium salt, the rest of the electrolyte is an organic solvent. In this embodiment, the thickness of the lithium metal after pre-lithiation of the negative electrode is 1μm. The above components are mixed to obtain an electrolyte. In Table 1, the content of each component except the solvent is the weight percentage calculated based on the total weight of the electrolyte. The preparation method of the electrolyte in other embodiments is the same as that of this embodiment, except that the component ratio is specified in the table.

[0047] Example 2

[0048] The difference between this embodiment and embodiment 1 is that the mass fraction of the FEC additive is 5%, and the rest is the same as embodiment 1.

[0049] Example 3

[0050] The difference between this embodiment and embodiment 1 is that the mass fraction of the FEC additive is 1%, and the rest is the same as embodiment 1.

[0051] Example 4

[0052] The difference between this embodiment and embodiment 1 is that the mass fraction of the FEC additive is 15%, and the rest is the same as embodiment 1.

[0053] Example 5

[0054] The difference between this embodiment and embodiment 1 is that the lithium salt in the electrolyte includes 14% lithium hexafluorophosphate (LiPF6) and 2% lithium bis(fluorosulfonyl)imide (LiFSI) in a mass fraction in the electrolyte, and the rest is consistent with embodiment 1.

[0055] Example 6

[0056] The difference between this embodiment and embodiment 1 is that the diluent is fluorobenzene, and the rest is the same as embodiment 1.

[0057] Example 7

[0058] The difference between this embodiment and embodiment 1 is that the diluent is 1,3,5-trifluorobenzene, and the rest is the same as embodiment 1.

[0059] Comparative Example 1

[0060] The difference between this comparative example and Example 1 is that no diluent is added to the electrolyte, and the rest is consistent with Example 1.

[0061] Comparative Example 2

[0062] The difference between this comparative example and Example 1 is that no FEC additive is added to the electrolyte, and the rest is the same as Example 1.

[0063] Comparative Example 3

[0064] The difference between this comparative example and Example 1 is that the diluent is fluorobenzene, no FEC additive is added to the electrolyte, and the negative electrode of the lithium-ion battery of this comparative example is not treated by pre-lithiation technology. The rest is consistent with Example 1.

[0065] Comparative Example 4

[0066] The difference between this comparative example and Example 1 is that the negative electrode of the lithium-ion battery in this comparative example is not treated by the pre-lithiation technology, and the rest is consistent with Example 1.

[0067] Table 1. Electrolyte compositions of different groups of examples and comparative examples

[0068]

[0069]

[0070] The electrolytes of Examples 1 to 7 and Comparative Examples 1 to 4 were respectively used in the preparation of lithium ion batteries.

[0071] In the embodiment of the present invention, the electrochemical device is a lithium-ion battery, and the lithium-ion battery is a primary lithium-ion battery or a secondary lithium-ion battery, including: a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode and the negative electrode, and an electrolyte. The preparation method of the secondary lithium-ion battery in the embodiment of the present invention is as follows:

[0072] (1) Preparation of lithium nickel cobalt manganese oxide positive electrode

[0073] The positive electrode active material (LiNi 0.8 Co 0.1 Mn 0.1O2), polyvinylidene fluoride as a binder and Super P as a conductive agent are mixed in a weight ratio of 98:1:1, and then N-methylpyrrolidone (NMP) is added to the mixture. The mixed system is stirred by a vacuum mixer until it becomes a uniform and transparent mixed solution to obtain the positive electrode slurry; the positive electrode slurry is evenly coated on the aluminum foil; the aluminum foil is dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain the positive electrode sheet.

[0074] (2) Preparation of graphite-silicon composite negative electrode sheet:

[0075] A mixture obtained by mixing artificial graphite with a silicon-carbon composite in a mass ratio of 9:1 is used as a negative electrode active material, Super P is used as a conductive agent, sodium carboxymethyl cellulose (CMC-Na) is used as a thickener, and styrene-butadiene rubber (SBR) is used as a binder. The above negative electrode active material, conductive agent, thickener, and binder are mixed in a mass ratio of 96:1:1:2, deionized water is added, and the above mixed substances are stirred evenly by fully stirring with a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; the copper foil is then dried at room temperature and then transferred to an oven for drying, and finally cold pressed, resistive thermal evaporation is used to deposit 1μm lithium metal, and the negative electrode sheet is cut.

[0076] (3) Preparation of electrolyte

[0077] In an argon atmosphere glove box with a water content of <10ppm, battery-grade ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 1:2:1:6 to form an organic solvent. The types of lithium salts, diluents, and additives selected in the electrolytes in Examples 1-7 of the present invention and Comparative Examples 1-4 and the mass fractions based on the total weight of the electrolyte are all based on the settings in Table 1 above. In addition to the diluent, additives, and lithium salts in the electrolyte, the remaining part is an organic solvent. The above components are mixed to obtain an electrolyte. In Table 1, the content of each component except the solvent is the mass percentage calculated based on the total mass of the electrolyte; the electrolytes in different embodiments and comparative examples are prepared in the same manner except that the component ratios are specified in the table.

[0078] (4) Preparation of isolation membrane

[0079] A 12 μm polypropylene film (PP) was selected as the isolation film.

[0080] (5) Preparation of secondary lithium-ion batteries

[0081] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in sequence, so that the separator is placed between the positive and negative electrode sheets to play an isolating role. Then, the sheet is wrapped with aluminum plastic film, transferred to a vacuum oven for drying at 120°C, injected with 3.0g / Ah of the electrolyte prepared above, and sealed, and left to stand at 25°C for 48h to complete the pre-lithiation of the negative electrode, and further electrolyte formation is performed, and finally a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah is prepared.

[0082] The performance of lithium-ion batteries assembled from the electrolytes in Examples 1-7 and Comparative Examples 1-4 was tested. The test results are shown in Table 2. The test method is as follows:

[0083] (1) Secondary lithium-ion battery first performance test

[0084] The secondary battery was placed in a thermostat at 25°C and allowed to stand for a long time. After standing for a long time, the battery was charged at a rate of 0.333C to a cut-off voltage, and then discharged at a rate of 0.333C to a cut-off voltage. The percentage of the discharge capacity to the sum of the formation capacity and the initial charge capacity was compared.

[0085] (2) Secondary lithium-ion battery cycle test

[0086] In an oven at a specified temperature (room temperature 25°C or high temperature 45°C), cyclic charge and discharge are performed at a current of 1C in a specified potential range, and the discharge capacity of each cycle is recorded. The test is terminated when the battery capacity reaches 80% of the first cycle capacity.

[0087] (3) Secondary lithium-ion battery DC resistance (DCR) test

[0088] At a specified temperature, when the battery is discharged to 50% SOC (state of charge, reflecting the remaining capacity of the battery) at a current of 1C, the current is increased to 4C and maintained for 30s. The difference between the updated stable voltage and the original platform voltage is detected. The ratio of its value to the 4C current value is the DC resistance of the battery. The DCR test result after the battery is fully charged for the first time is the initial DCR of the battery.

[0089] (4) Secondary lithium-ion battery high temperature storage DC resistance (DCR) test

[0090] After the formed battery is charged to the cut-off voltage at room temperature with 1C constant current and constant voltage, it is discharged to 50% SOC with 1C current, and then discharged for 30s at 4C to test DCR, which is recorded as DCR0. Then, after discharging to the cut-off voltage with 1C, it is charged to the cut-off voltage with 1C constant current and constant voltage, and stored at 60℃ for 90 days. After the battery cools to room temperature, the DCR is tested under the same conditions, which is recorded as DCR 90 , the DCR storage growth rate is (DCR 90 / DCR 0-1 )*100%.

[0091] For lithium nickel cobalt manganese oxygen / silicon-graphite batteries, the charge and discharge cut-off voltage is: 2.5-4.25V.

[0092] The test results are shown in Table 2

[0093] Table 2. Performance test results of lithium-ion batteries of different groups of examples and comparative examples

[0094]

[0095] Analyzing the above data, we can draw the following conclusions:

[0096] By comparing Example 1 with Comparative Example 1, it can be seen that the use of an electrolyte containing a diluent can enhance the initial efficiency of a lithium-ion battery and improve impedance, room temperature cycle, and high temperature storage performance.

[0097] From the comparison between Example 1 and Comparative Example 2, it can be seen that if the FEC additive is not added to the electrolyte, the room temperature cycle and high temperature storage performance of the lithium-ion battery will be greatly deteriorated.

[0098] By comparing Example 1 with Comparative Example 4, it can be seen that the first efficiency of the lithium-ion battery can be greatly improved and the cycle life at room temperature can be increased after the negative electrode is treated with the pre-lithiation technology.

[0099] From the comprehensive comparison of Examples 1 to 4, it can be seen that when the mass fraction of the FEC additive in the electrolyte is 1%-20%, within this mass range, when the amount of the FEC additive is slightly increased, the first efficiency and impedance of the lithium-ion battery will be slightly deteriorated, but its room temperature cycle and high temperature storage performance can be improved. However, when the amount of the FEC additive is too high, the impedance of the lithium-ion battery deteriorates more, and there is no obvious improvement in its room temperature cycle. The mass fraction of the FEC additive in the electrolyte is preferably 1-10%.

[0100] From the comparison between Example 1 and Example 5, it can be seen that replacing LiFSI with LiPF6 as the lithium salt of the electrolyte will cause a certain deterioration effect on the first efficiency, impedance, room temperature cycle, and high temperature storage performance of the lithium-ion battery.

[0101] By comparing Example 6 with Example 1, it can be seen that the use of a diluent with lower viscosity can improve the impedance of the battery; by comparing with Comparative Example 3, it can be seen that if no FEC additive is added to the electrolyte and the negative electrode is not treated with pre-lithiation technology, the first efficiency, room temperature cycle life and high temperature storage performance of the lithium-ion battery will all be at a poor level.

[0102] From the comparison between Example 7 and Example 1, it can be seen that the use of a more stable diluent can improve the high temperature performance of the battery.

[0103] Based on the above performance comparison results:

[0104] By comparing Examples 1 to 7 with Comparative Examples 3 to 4, it can be seen that after the negative electrode of the lithium-ion battery is pre-lithiated, the active lithium in the battery is supplemented, which significantly improves the first effect and cycle life of the lithium-ion battery, and at the same time does not cause significant deterioration in the impedance of the battery. In addition, due to the addition of FEC additives to the electrolyte, the negative electrode surface consumes the residual lithium metal that can become a lithium precipitation site and forms a dense SEI film. Although the first effect of the lithium-ion battery will be reduced to a certain extent due to the addition of FEC additives, its normal temperature cycle life is improved, and its high temperature performance is also significantly improved.

[0105] By comparing Examples 1 to 7 with Comparative Examples 1 to 2, it can be seen that the use of an electrolyte containing a diluent for negative electrode pre-lithiation has a more significant improvement in the first effect and cycle life than ordinary carbonate electrolytes, because the solvent of ordinary carbonate electrolytes is easily reduced during the pre-lithiation process, forming a loose organic SEI layer, which can easily cause the lithium metal on the surface to reduce the carbonate solvent molecules in the electrolyte, resulting in low utilization of lithium metal, and the gas generated by the side reaction will further damage the interface layer on the electrode surface, deteriorating the performance of the battery cell, resulting in poor negative electrode pre-lithiation effect. The electrolyte in the embodiment of the present invention effectively overcomes the above problems when performing negative electrode pre-lithiation.

[0106] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for pre-lithiation of a negative electrode plate, characterized in that: The following steps are involved: A film forming step, forming a lithium metal film on the surface of the negative electrode plate; The formation step is to place the negative electrode sheet with the lithium metal film in an electrolyte to obtain a pre-lithiated negative electrode sheet. The electrolyte used in the formation step comprises: Organic solvents; A lithium salt is dissolved in the organic solvent, wherein the mass fraction of the lithium salt in the electrolyte is 10%-20%; A diluent, wherein the diluent is a substituted or unsubstituted aromatic compound, and the mass fraction of the diluent in the electrolyte is 20-50%; The additive is a fluorinated carbonate additive having a reduction potential higher than that of the organic solvent, and the mass fraction of the fluorinated carbonate additive in the electrolyte is 1%-20%.

2. The method for pre-lithiation of a negative electrode sheet according to claim 1, characterized in that: The fluorinated carbonate additive is fluorinated ethylene carbonate, and the mass fraction of the fluorinated ethylene carbonate in the electrolyte is 1-10%.

3. The method for pre-lithiation of a negative electrode sheet according to claim 1, characterized in that: In the film forming step, the lithium metal film is formed on the surface of the negative electrode plate by physical vapor deposition or roll-compression lamination, and the thickness of the lithium metal film is 0.5-10 μm.

4. The method for pre-lithiation of a negative electrode sheet according to claim 1, characterized in that: In the formation step, a prescribed standing temperature is used for a prescribed time, wherein the prescribed standing temperature is 25° C.-60° C., and the prescribed time is 24 h-96 h.

5. A lithium ion battery, characterized in that: include: Negative electrode; Positive electrode; and An electrolyte, wherein the negative electrode plate and the positive electrode plate are separated and arranged in the electrolyte, the surface of the negative electrode plate has a pre-lithiation layer, and the pre-lithiation layer is obtained by forming a lithium metal film covering the surface of the negative electrode plate in the electrolyte, and the electrolyte comprises: Organic solvents; A lithium salt is dissolved in the organic solvent, wherein the mass fraction of the lithium salt in the electrolyte is 10%-20%; A diluent, wherein the diluent is a substituted or unsubstituted aromatic compound, and the mass fraction of the diluent in the electrolyte is 20-50%; The additive is a fluorinated carbonate additive having a reduction potential higher than that of the organic solvent, and the mass fraction of the fluorinated carbonate additive in the electrolyte is 1%-20%.

6. The lithium ion battery according to claim 5, characterized in that The fluorinated carbonate additive is fluorinated ethylene carbonate, and the mass fraction of the fluorinated ethylene carbonate in the electrolyte is 1-10%.

7. The lithium ion battery according to claim 5, characterized in that The diluent includes at least any one of fluorobenzene, o-difluorobenzene, m-difluorobenzene, p-difluorobenzene, 1,3,5-trifluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, trifluoromethylbenzene, toluene and ethylbenzene, or a combination of at least two thereof.

8. The lithium ion battery according to claim 5, characterized in that The organic solvent includes any one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate, or a combination of at least two thereof, and the mass fraction of the organic solvent in the electrolyte is 30%-65%.

9. The lithium ion battery according to claim 5, characterized in that The positive electrode plate includes a positive electrode current collector and a positive electrode active material, and the positive electrode active material includes any one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, or a combination of at least two thereof.

10. The lithium ion battery according to claim 5, characterized in that The negative electrode plate includes a negative electrode current collector and a negative electrode active material, and the negative electrode active material includes any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide, silicon carbon compound or lithium titanate, or a combination of at least two thereof.

Citation Information

Cited By

  • A method for pre-lithiation of a negative electrode sheet of a lithium-ion battery and a negative electrode sheet of a lithium-ion battery

    CN119764351A

  • Composite electrode tab, method of making the same, and battery

    CN122781807A